«Արաբական գարունը» Մաղրիբում և Թուրքիան - Ժամհարյան, Արմեն (YSU Journal of International Affairs, 2014)
The article presents the relationship between Turkey and Arab Maghreb countries in theArab Spring. Particular emphasis was placed on the Turkish model and the ArabMaghreb countries’ positions towards it. There are also introduced parties desire toimitate the Turkish mode which came to power in Maghreb. Also attention was paid tothe Turkish policy towards the Maghreb countries during the Arab Spring. That policyaimed to protect and strengthen its position in the region which has a significant importance for Turkey. Submitting these and other developments, the article concludes thatduring the Arab Spring Turkey's policy was successful to a large extent.
Keywords: Arab Spring, the Arab Maghreb, Turkey, Islamic party, revolution, political, “Turkish model”, democracy, extremist, moderate, influence